Untersuchung der Auswirkungen einer RFID-gestützten Bauzustandsdokumentation auf die Dokumentationsqualität in der Erprobungsphase : am Beispiel ausgewählter Baureihen eines Automobilunternehmens - Kovac, Florian (Wissenschaftliche Berichte des Institutes für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2013)
The testing of prototype vehicles under real conditions is an essential part of the vehicle development. An up-to-date and accurate documentation of the vehicle configuration is an important factor for an effective analysis of test drives. The RFID technology provides several benefits by automatic identification of objects. In the context of this work it is shown that a better quality of the documentation of the state of construction compared with conventional documentation methods is possible.